Phyllocnistis hemera sp. nov. (Lepidoptera: Gracillariidae): a new species of leaf-miner associated with Daphnopsis fasciculata (Thymelaeaceae) in the Atlantic Forest - Fochezato,Júlia (2018)
ABSTRACT During recent studies performed in the Atlantic Forest, a new species of Phyllocnistinae (Gracillariidae), Phyllocnistis hemera sp. nov., leaf miner of Daphnopsis fasciculata (Thymelaeaceae) was discovered. The adults are described and illustrated as well as the immature stages, with notes on natural history including a description of the leaf mine. Additionally, DNA barcode sequences were compared to other representatives of Phyllocnistinae to test for the specific status of P. hemera and to infer phylogenetic relationships. This is the fifth species described for the genus Phyllocnistis in the Atlantic Forest and the first record of a gracillarid mining Thymelaeaceae leaves.